The Protective Effect of Metformin on Abdominal Aortic Aneurysm: A Systematic Review and Meta-Analysis - Yuan, Zhen; Heng, Zhijian; Lu, Yi; Wei, Jia; Cai, Zhejun (Frontiers in Endocrinology, 2021)
Background Type 2 diabetes mellitus (T2DM) patients have a lower risk of abdominal aortic aneurysm (AAA) and its comorbidities, which might be associated with the usage of metformin. The objective of the study was to evaluate the role of metformin in the process of AAA development. Method PubMed, Embase and Cochrane Library were searched up to May 15th, 2021. We implemented several methods including the risk of bias graph, GRADE system and funnel plot to assess the quality and possible bias of this study. Subgroup analysis and sensitivity analysis were applied to address quality differences and validate the robustness of the final results. Result Ten articles were enrolled after screening 151 articles searched from databases. The pooled results showed that, compared with T2DM patients without metformin, metformin prescription was associated with a slower annual growth rate of the aneurysm (mean difference (MD) -0.67 cm [95% confidence interval (CI) -1.20 ~ -0.15 cm]). Besides, metformin exposure was associated with a lower frequency of AAA events (odds ratio (OR) 0.72 [95% CI 0.55-0.95]). Conclusion Metformin alleviated both annual expansion rate and aneurysm rupture frequency in AAA patients with T2DM. Trial registration PROSPERO registration number: CRD42020217859